2013
DOI: 10.1080/02699931.2013.809331
|View full text |Cite
|
Sign up to set email alerts
|

Visual search for schematic emotional faces: Angry faces are more than crosses

Abstract: Recent studies of the face in the crowd effect, the faster detection of angry than of happy faces in visual search, suggest that for schematic faces it reflects on perceptual features like inward pointing lines rather than on emotional expressions. Removing a potential confound, Experiments 1-2 replicate the preferential detection of stimuli with inward pointing lines, but Experiment 2a indicates that a surrounding circle is required for the effect to emerge. Experiments 3-7 failed to find evidence for faster … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(12 citation statements)
references
References 19 publications
0
12
0
Order By: Relevance
“…Importantly though the same was also the case for the abstract stimuli. This suggests that there is at least some contribution to the effect other than what might be caused by interactions between the inner and outer line components that are present with surrounds, as suggested by Coelho et al (2010), Purcell and Stewart (2010), and Dickins and Lipp (2014), for example. It should also be noted that the removal of the surrounds greatly improved the overall accuracy rate of Experiment 2 compared with Experiment 1, even though the experiments were conducted in the same manner on a similar student population.…”
Section: Discussionmentioning
confidence: 85%
See 1 more Smart Citation
“…Importantly though the same was also the case for the abstract stimuli. This suggests that there is at least some contribution to the effect other than what might be caused by interactions between the inner and outer line components that are present with surrounds, as suggested by Coelho et al (2010), Purcell and Stewart (2010), and Dickins and Lipp (2014), for example. It should also be noted that the removal of the surrounds greatly improved the overall accuracy rate of Experiment 2 compared with Experiment 1, even though the experiments were conducted in the same manner on a similar student population.…”
Section: Discussionmentioning
confidence: 85%
“…They suggested that the radial lines of the angry-face, cross-, or plus-shaped stimuli might interact with the surround to produce a T-shaped junction and that this might serve as a basic search feature. However, in the interim, Dickins and Lipp (2014), reported that although removing the surrounds from the abstract shapes reduced the search advantage for the angry faces, the predicted difference was still evident (albeit not statistically significant). In this current paper we sought to investigate this further.…”
Section: Discussionmentioning
confidence: 94%
“…The target sample size was based on previous studies investigating visual search biases with face targets (e.g., Dickins & Lipp, [emotion]; Levin, [race]). Based on past studies, we recruited until at least 20 participants had signed up for each study and stopped testing once all recruited participants had taken part.…”
Section: Methodsmentioning
confidence: 99%
“…Frischen et al () reviews evidence suggesting that facial expressions of emotions pop out. The so‐called “face in the crowd” effect is related: angry faces pop out more readily than other faces (Fox et al , Öhman et al , Pinkham et al , Dickins and Lipp ). Why not think that it is just a certain configuration of the face that pops out?…”
Section: The Psychological Thesismentioning
confidence: 99%